Chapter 4 Posting of Workers During the Covid-19 Pandemic in the European Union The Case of Slovenia - zirnstein, elizabeta (Routledge Studies in Labour Economics, 2023)
The free movement of services, one of the four fundamental freedoms of the European Union's (EU) internal market, allows companies to post their employees to other EU Member States. In Slovenia, the concept of cross-border posting became relevant after the country joined the EU in 2004. The number of posted workers in Slovenia has been growing steadily since then and is among the highest in the EU. An increase in posting has also been observed in the EU as well. One of the main reasons for the rapid increase in the number of workers posted to wealthier EU countries is the accession of ten new Member States in 2004, with significant differences in living standards between the `new´ and `old´ Member States. Focusing on Slovenia, an important reason for Slovenia's high numbers of posted workers is also its proximity to the countries of the former Yugoslavia and the strong migrant flows from these countries to the EU via Slovenian companies. As a result, the number of workers posted from Slovenia to other EU Member States has been one of the highest in the EU over the past decade.